2012
DOI: 10.1038/bjc.2012.437
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II trial of a biweekly combination of S-1 plus docetaxel in patients with previously treated non-small cell lung cancer (KRSG-0601)

Abstract: Background:Combination of S-1, an oral fluorouracil derivative, plus docetaxel against non-small cell lung cancer (NSCLC) showed promising efficacy but clinically problematic emesis. A phase I/II study utilising a new schedule for this combination was conducted.Methods:A biweekly regimen of docetaxel on day 1 with oral S-1 on days 1–7 was administered to previously treated NSCLC patients. Doses of docetaxel/S-1 were escalated to 30/80, 35/80, and 40/80 mg m−2, respectively, and its efficacy was investigated at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Approximately 54% of patients present a metastasis at diagnosis due to lack of clinical symptoms at the early stages, which tends to result in an extremely poor prognosis with an overall 5-year survival rate of 3.8% 12. For most advanced lung cancers, standard chemotherapy involving pemetrexed,13,14 oxaliplatin,15 and docetaxel,16 is generally the mainstream of management, but apparently this has reached a plateau with disappointing outcomes 17. Despite the introduction of a series of targeted drugs for patients with epidermal growth factor receptor mutations (gefitinib or erlotinib)18,19 and ALK rearrangement (crizotinib)20 in the past decade, the survival rate still has not been significantly improved.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 54% of patients present a metastasis at diagnosis due to lack of clinical symptoms at the early stages, which tends to result in an extremely poor prognosis with an overall 5-year survival rate of 3.8% 12. For most advanced lung cancers, standard chemotherapy involving pemetrexed,13,14 oxaliplatin,15 and docetaxel,16 is generally the mainstream of management, but apparently this has reached a plateau with disappointing outcomes 17. Despite the introduction of a series of targeted drugs for patients with epidermal growth factor receptor mutations (gefitinib or erlotinib)18,19 and ALK rearrangement (crizotinib)20 in the past decade, the survival rate still has not been significantly improved.…”
Section: Discussionmentioning
confidence: 99%
“…## p<0.01 versus Anti-miRNA-NC group. for surgery (13). In consequence, chemotherapy has become the main treatment method of NSCLC (14).…”
Section: Discussionmentioning
confidence: 99%
“…Among nonhematologic toxicities, stomatitis and diarrhea tended to be more common compared with the results of other concomitant treatments. This could have been due to S‐1, but the incidence was higher than that reported with S‐1 alone and with DOC + S‐1 combination therapy . Conversely, in a report of a phase II study of S‐1 + PTX in gastric cancer, stomatitis of grade 3 or higher was reported in 28% ; caution should be exercised in interpreting these results as these mucosal lesions may have been increased owing to PTX.…”
mentioning
confidence: 85%